Reframing Africa? Reflections on Modernity and the Moving Image - Kros, Cynthi; Auguiste, Reece; Khan, Pervaiz (African Minds, 2022)
This book takes readers on a series of stimulating intellectual journeys from the late nineteenth century to the contemporary era to explore notions of modernity in the production and reception of the African moving image and of African archival practices. Ideas are presented from multiple historical and contemporary perspectives, while inviting new voices to participate in discussions about the future of the African moving image. Reframing Africa?makes a plea for the recognition, preservation and repatriation of the African moving image archive, advancing ideas about how it speaks to contemporary Africans, possessed of the power to elucidate their lived experiences and to reorientate perceptions of the past, present and future. On the basis of this wide-ranging appreciation of the archive, the book charts a way forward for African-inflected film studies as well as other programmes in the humanities and social sciences. Reframing Africa? will appeal to scholars, academics and practitioners across the continent and beyond.